The mechanism of coumarin inhibits germination of ryegrass (Lolium perenne) and its application as coumarin–carbon dots nanocomposites. Issue 6 (3rd March 2023) - Yang, Ni; He, Xiulong; Ran, Lulu; Yang, Furong; Ma, Chuanxin; Chen, Hanqiu; Xiang, Dong; Shen, Guangmao; Zhang, Ping; He, Lin; Qian, Kun
Abstract: BACKGROUND: As an important plant allelochemical, coumarin can effectively inhibit the germination of various seeds. However, little is known about the inhibition mechanism of coumarin on weed seed germination. Moreover, the herbicidal activity of coumarin is needed to be improved as a natural pesticide. RESULTS: Coumarin had the highest inhibition effect on the ryegrass ( Lolium perenne ) seed, where coumarin disturbed the hormone pathway by decreasing the content of gibberellic acid 3, resulting in the reduction of amylase activity and consumption of starch during the germination process of ryegrass seed. Moreover, coumarin induced decreased activity of catalase and subsequently led to the accumulation of hydrogen peroxide and malondialdehyde, causing oxidative stress during the germination process of ryegrass seed. Furthermore, to enhance the herbicidal activity of coumarin, carbon dots (CDs) modified with polyetherimide were prepared, characterized, and then combined with coumarin to form coumarin–carbon dots (Cm‐CDs) nanocomposites. Compared with coumarin, Cm‐CDs nanocomposites significantly increased the herbicidal activity of coumarin on ryegrass, which implies that Cm‐CDs nanocomposites could be used as a potential formulation to improve the herbicidal activity of coumarin. CONCLUSION: This study not only reveals the mechanism of coumarin on ryegrass germination, but also develop Cm‐CDs nanocomposites to enhance the herbicidal activity of coumarin. Our findings will stimulate the application of Cm‐CDs nanomaterials as an effective and environmentally friendly formulation in agriculture. © 2023 Society of Chemical Industry. Abstract : Coumarin‐carbon dots (Cm‐CDs) nanocomposites inhibit germination of ryegrass ( Lolium perenne ): mechanism and application.